2021
DOI: 10.3892/etm.2021.9819
|View full text |Cite
|
Sign up to set email alerts
|

Oroxylin A attenuates IL‑1β‑induced inflammatory reaction via inhibiting the activation of the ERK and PI3K/AKT signaling pathways in osteoarthritis chondrocytes

Abstract: Osteoarthritis (OA) is characterized by degradation of the articular cartilage, synovium inflammation, subchondral bone sclerosis and osteophyte formation. OA is the most common degenerative joint disorder among the elderly population. In particular, currently available therapeutic strategies, such as non-steroidal anti-inflammatory drugs (NSAIDs) may cause severe side-effects. Therefore, novel candidate targets for OA therapy are urgently needed. Oroxylin A (OrA) is a natural mono-flavonoid that can be extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
3
8
0
Order By: Relevance
“…Studies also revealed that the PI3K/AKT/mTOR pathway plays a crucial role in cartilage degradation and can be used as a therapeutic target for the clinical intervention of OA (41,42). Consistently, we identified the signaling proteins that are enriched in PI3K/AKT pathway (Figure S2) and the perturbagens that inhibit the PI3K/AKT signaling pathway, including oroxylin A (43), KU-0063794 (44), and other novel perturbagens such as NVP-BEZ235 and TG100-115 (Table S4). In addition, previous reports have indicated that VEGF can be a biomarker for patients with OA, which is highly expressed in articular cartilage, synovium, subchondral bone and serum of OA patients (45).…”
Section: Resultssupporting
confidence: 60%
“…Studies also revealed that the PI3K/AKT/mTOR pathway plays a crucial role in cartilage degradation and can be used as a therapeutic target for the clinical intervention of OA (41,42). Consistently, we identified the signaling proteins that are enriched in PI3K/AKT pathway (Figure S2) and the perturbagens that inhibit the PI3K/AKT signaling pathway, including oroxylin A (43), KU-0063794 (44), and other novel perturbagens such as NVP-BEZ235 and TG100-115 (Table S4). In addition, previous reports have indicated that VEGF can be a biomarker for patients with OA, which is highly expressed in articular cartilage, synovium, subchondral bone and serum of OA patients (45).…”
Section: Resultssupporting
confidence: 60%
“…Previous studies reported the inhibition of AKT activation by 4-MU in cancer cell line, such as prostate cancer [ 37 ], osteosarcoma [ 38 ], and breast cancer [ 39 ]. Recent study reported that MMP-3 and -13 was induced by IL-1β via PI3K/AKT signaling pathways in chondrocytes [ 40 ]. In tumor cells, PI3K/Akt signaling pathway is reported to involve cell proliferation and apoptosis via CD44/HA interaction [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, OA inhibited the expression of several pro-inflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α) and interleukins (IL-1β, IL-4, IL-6, IL-13) [ 69 , 70 ]. Apart from these, OA was also shown to reduce the expression of enzymes, including cyclooxygenase 2 (cox-2), inducible nitric oxide synthase (iNOS), glycogen synthase kinase 3-β (GSK-β), lactate dehydrogenase (LDH), pyruvate kinases isozymes (PKM1/PKM2), etc., which envisages its anti-inflammatory properties [ 71 , 72 ].…”
Section: Molecular Targets Of Oamentioning
confidence: 99%
“…Besides, OA attenuated IL-1β-stimulated upregulation of MMP-3 and MMP-13 expression, disintegrin, and matrix metalloproteinase with thrombospondin motifs, ADAMTS-4 and ADAMTS-5 expression. Furthermore, OA suppressed the activation of ERK 1/2 and PI3K/Akt signaling pathways and caused the reversal of IL-1β-induced type II collagen and aggrecan degradation [ 72 ]. Both studies suggest that OA could be a potential therapeutic agent for osteoarthritis.…”
Section: Oa For Inflammatory Diseasesmentioning
confidence: 99%